Analisis Pengaruh Kualitas Produk, Premi Dan Kualitas Layanan Klaim Dalam Meningkatkan Minat Beli Ulang Pelanggan Melalui Keunggulan Kompetitif Asuransi Kesehatan Di PT. Asuransi Jiwa Inhealth Indonesia - Nuraini; Widyastuti, Sri; Supriyadi, Eddy (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
The purpose of this study was to determine the effect of product quality, premiums and service quality claims on customer repurchase interest through the competitive advantage of health insurance at PT. Asuransi Jiwa Inhealth Indonesia. The sampling technique is total sampling, which is a sample that represents the total population. Collecting data using a questionnaire. The data analysis technique used Structural Equation Modeling (SEM) analysis processed with SmartPLS software. The results showed that the variable product quality and service quality claims have a significant effect on competitive advantage, while the premium variable has no significant effect on competitive advantage. The premium variable has a significant effect on repurchase interest, while the product quality and claims service quality variables have no significant effect on repurchase interest. The competitive advantage variable has a significant effect on repurchase interest. The results also show the most dominant direct influence, namely the direct influence between claim service quality on competitive advantage and the most dominant indirect effect between the variables, namely the influence of claim service quality through competitive advantage on repurchase interest